Management of Hepatitis C Infection with Direct Action Antiviral Drugs (DAA)** - Roberto Focaccia; Rodolfo Ferreira de Mello; Patrícia Silva Montes; Flávio Martin Conti (Archives of Hepatitis Research - Peertechz Publications, 2015)
Several new direct action antiviral drugs (DAA) against the HCV virus (HCV) are approved and marketed. The combination of DAA with pegylated interferon and ribavirin (PR) is only recommended to patients with tolerance to interferon (IFN). IFN-free treatments are now considered elective drugs for patients with  chronic HCV. More than 90% of patients infected with HCV genotype 1 or 4 (fewer with other genotypes) show sustained virological response, when treated with sofosbuvir combined with simeprevir, daclatasvir or ledipasvir, or by the combination of paritaprevir with ritonavir, ombitasvir and dasabuvir, with or without ribavirin. The safety and efficacy of DAA therapy in HIV-HCV confection is now comparable with HCV monoinfection. DAA drugs are also efficient in patients with previous interferon/ribavirin, or protease inhibitors, treated patients as well as with hepatic transplanted patients. The goal of this review is to clarify the current stage of DAA drugs already approved and available by January-2016. Another objective is to discuss the main drugs regimen recommended by international medical associations and drugs regulatory agencies, including Brazil's Health Ministry. In this review, the authors make an approach about: adverse effects of DAA; interactions with other drugs, efficacy in patients with compensated cirrhosis or comorbidities, different genotypes or subtypes, as well as the development of resistance associated to viral mutants and their possible clinical importance.